Nano-mechanical Characterization of Mg-Zn-Mn-Si Alloy Fabricated by Spark Plasma Sintering for Biomedical Applications. (2018) - Singh, Bhupinderpal; Singh, Ramandeep; Mehta, J.S.; Gupta, Anjali; Singh, Manjeet; Singh, Sunpreet; Prakash, Chander
Abstract: Here in, a bio-inspired biodegradable Mg-Zn-Mn-Si Alloy was synthesised by mechanical alloying and spark plasma technique. The effect milling time, sintering temperature, and sintering pressure has been studied on the elastic modulus and hardness of the as-synthesized alloy. The microstructure, surface topography, and element composition as-synthesized alloy was investigated using optical microscope, field-emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The elastic modulus and hardness of as-synthesized alloy was measured by nano-indentation technique. The microstructure examination of the compact reveled that Si not only refined the gain structure but also formed Mg2 Si in the structure. XRD pattern analysis confirmed the formation of Mg2 Si, Mg-Zn, Mn-Si, SiO2, and ZnO2 due to heat developed during the process, which enhanced the mechanical properties and corrosion characteristics